Food Restriction Enhances the Central Rewarding Effect of Abused Drugs - Cabeza de Vaca, Soledad (J Neurosci, 1998)
Chronic food restriction increases the systemic self-administration and locomotor-stimulating effect of abused drugs. However, it is not clear whether these behavioral changes reflect enhanced rewarding potency or a CNS-based modulatory process. The purpose of this study was to determine whether food restriction specifically increases the rewarding potency of drugs, as indexed by their threshold-lowering effect on lateral hypothalamic self-stimulation, and whether any such effect can be attributed to an enhanced central response rather than changes in drug disposition. When drugs were administered systemically, food restriction potentiated the threshold-lowering effect of amphetamine (0.125, 0.25, and 0.5 mg/kg, i.p.), phencyclidine (1.0, 2.0, and 3.0 mg/kg, i.p.), and dizocilpine (MK-801) (0.0125, 0.05, and 0.1 mg/kg, i.p.) but not nicotine (0.15, 0.3, 0.45 mg/kg, s.c.). When amphetamine (25.0, 50.0, and 100.0 μg) and MK-801 (5.0, 10.0, and 20.0 μg) were administered via the intracerebroventricular route, food restriction again potentiated the threshold-lowering effects and increased the locomotor-stimulating effects of both drugs. These results indicate that food restriction increases the sensitivity of neural substrates for rewarding and stimulant effects of drugs. In light of work that attributes rewarding effects of MK-801 to blockade of NMDA receptors on medium spiny neurons in nucleus accumbens, the elements affected by food restriction may lie downstream from the mesoaccumbens dopamine neurons whose terminals are the site of amphetamine-rewarding action. Possible metabolic–endocrine triggers of this effect are discussed, as is the likelihood that mechanisms mediating the modulatory effect of food restriction differ from those mediating sensitization by intermittent drug exposure.